2015 Annual Conference: Keynote address: Trusting the scientist - Gluckman, Peter (New Zealand Science Review, 2015)
​We live in a world that is often characterised as a post-trust society (1), in which the processes of societal decision-making and public reasoning have been dramatically changed by access to much more information and opinion via a variety of new media, and this content is of highly variable reliability. With this nearly boundless access to news and information, many of the claims and counterclaims about science can be conflicting and confusing, and they can be manipulated by many stakeholders, including scientists themselves, for particular goals. Yet at the same time, there has never been a more urgent need and expectation for an active role for applying scientific knowledge and expertise in the processes of developing societal consensus, of governing, and of law-making. Indeed, virtually every major challenge a society such as ours faces today requires increasingly sophisticated scientific input, from the physical, natural, or social sciences. While it is clear that science alone cannot provide answers to societal and environmental challeng-es, it does provide a broader and more knowledgeable view of the various options. As such, it has truly become an essential tool of democracy.